1989
DOI: 10.1139/y89-232
|View full text |Cite
|
Sign up to set email alerts
|

Ductus arteriosus: involvement of a sarcolemmal cytochrome P-450 in O2 constriction?

Abstract: Our previous studies implicate a cytochrome P-450-based mechanism in the constrictor response of the ductus arteriosus to oxygen. The present experiments were conducted on saponin-skinned strips of ductal muscle from mature fetal lambs to determine the location, sarcolemmal versus intracellular, of this cytochrome and to obtain a better insight into the sequence of events underlying the action of oxygen. Skinned preparations contracted to free Ca2+ over the range between 0.1 and 5-10 microM (pCa 7 to 5). In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…6). The exact mechanisms that mediate this response are still unknown (14,17). Oxygen causes membrane depolarization, which, in turn, is associated with a rise in smooth muscle intracellular calcium (33).…”
Section: Discussionmentioning
confidence: 99%
“…6). The exact mechanisms that mediate this response are still unknown (14,17). Oxygen causes membrane depolarization, which, in turn, is associated with a rise in smooth muscle intracellular calcium (33).…”
Section: Discussionmentioning
confidence: 99%
“…A cytochrome P 450 hemoprotein, that is located in the plasma membrane of the vascular smooth muscle cells, appears to act as a receptor for the oxygen-induced events in the ductus [24,25] . Oxygen inhibits K + channels [26,27] .…”
Section: Regulation Of Ductus Arteriosus Patencymentioning
confidence: 99%
“…The purpose for CYP3A expression in this spatiotemporal distribution is unclear. The data of Coceani and colleagues provide strong evidence that a hemoprotein in the CYP3A family of enzymes endows the ductus with a fundamental mechanism for oxygen-sensing [46, 32, 33]. In this regard, we observed that the term gestation DA was more susceptible than the preterm DA to cimetidine-induced relaxation, corresponding to maturation-related changes in DA sensitivity to oxygen.…”
Section: Discussionmentioning
confidence: 55%
“…CO-induced relaxation was completely reversed by monochromatic light at 450nm wavelength, implicating the actions of a hemoprotein in the CYP family [4, 5]. Additional evidence suggested that the CYP moiety was localized in the DA smooth muscle since endothelium-stripped vessels were equally relaxed by CO and required an intact plasma membrane [4, 5, 33]. Subsequent electron microscopy studies showed immunoreactive localization of CYP3A enzymes in the plasma membrane and sarcoplasmic reticulum of cultured DA smooth muscle cells [32].…”
Section: Discussionmentioning
confidence: 99%